Food in the cold: exploring food security and sovereignty in Whitehorse, Yukon. Issue 1 (31st December 2022) - Blom, C.D.B.; Steegeman, P.; Voss, C.; Sonneveld, B.G.J.S.
ABSTRACT: Harsh weather patterns that are unpredictable owing to climate change, remoteness, dependence on food imports and limited local food production place Arctic and Subarctic food systems under serious pressure. The model of food sovereignty provides a surprisingly interesting contribution to address the food insecurity in these regions; it promotes long-term stable provision of healthy foods (sustainable) that are accessible to all (equity) and fosters local food production–consumption patterns (localisation). This study aims to deepen the understanding of food insecurity in the Subarctic regions and explores the possibilities for a food sovereignty approach at both individual and regional level. The study focuses on Whitehorse, capital of Yukon, Canada, and uses a cross-sectional online survey among residents of Whitehorse and semi-structured in-depth interviews with food-systems experts in Yukon. The findings indicated a need for affordable year-round local food production. Application of food sovereignty has provided the opportunities for local food procurement, innovation hubs, and several types of greenhouses including hydroponics and vertical farming, to work towards a more localised food system, thereby improving food security and sovereignty in Yukon. The findings constitute the scientific knowledge base for the formulation of prospective scenarios in the spirit of the food sovereignty theory.